2013
DOI: 10.1016/j.mimet.2013.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Control of gene expression in Helicobacter pylori using the Tet repressor

Abstract: The lack of a versatile system to control gene expression in Helicobacter pylori has hampered efforts to study H. pylori physiology and pathogenesis. To overcome these limitations, we evaluated the utility of an inducible system based on the well-characterized Tet repressor (TetR) and Tet operator (tetO). As validation of this system, we introduced three copies of tetO into the promoter region upstream of the cagUT operon (encoding two virulence factors required for function of the H. pylori Cag type IV secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…When cocultured in vitro with gastric epithelial cells, H. pylori forms structures termed "pili" at the bacterium-host cell interface (29)(30)(31)(32)(33)(34)(35)(36)(37). Previous studies reported that a cag PAI mutant strain does not produce pili (29,(31)(32)(33)(34)(35)(36), but thus far, there has been very little effort to identify specific genes that are required for pilus production.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When cocultured in vitro with gastric epithelial cells, H. pylori forms structures termed "pili" at the bacterium-host cell interface (29)(30)(31)(32)(33)(34)(35)(36)(37). Previous studies reported that a cag PAI mutant strain does not produce pili (29,(31)(32)(33)(34)(35)(36), but thus far, there has been very little effort to identify specific genes that are required for pilus production.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit anti-CagT antiserum has been described previously (32). To generate CagC antiserum, three peptides representing residues 31 to 46, 60 to 80, and 106 to 115 of CagC were synthesized (39, 40) (Covance, Princeton, NJ) (Fig.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations